ANALYSIS OF THE RESPONSE SPECTRUM OF NONLINEARITY, REPRESENTED BY THE DYNAMIC SATURATION FUNCTION, UNDER MULTI-FREQUENCY IMPACT - Gulin, S. P. (Radio Electronics, Computer Science, Control, 2024)
The method of analysis of spectrum of the set response of nonlinearity is offered, by the represented analytical transcendent function, at multifrequency influence on the basis of hypergeometrical function of Gausse. The got results allow to design the conduct of wide class of electronic devices and components in the modes of small and large signals with an arbitrary spectrum.